Swearing in Sport and Exercise: Development and Validation of a New Questionnaire - Noam Manor; Gershon Tenenbaum (Psychology International)
Swearing, a highly emotive form of expression, has recently attracted growing interest from researchers. Yet, swearing is still largely unexamined as a form of self-talk among professional athletes, coaches, and casual exercisers. This study aims to fill that gap by creating and validating the Use of Swear Words in Sport and Exercise Questionnaire (USWSEQ), an innovative instrument intended to assess how often athletes, coaches, and recreational exercisers utilize common swear words. The questionnaire was administered to 513 participants and underwent exploratory (n = 333) and confirmatory (n = 180) factor analyses to evaluate its content structure, reliability, and validity. Results confirmed a robust two-factor model: (1) Self/Other Degradation, and (2) Situational Swearing. Notably, the study emphasizes the complexity involved in researching language, because swear words can be semantically ambiguous, pragmatically flexible, and deeply embedded in culture. These attributes present challenges for conventional psychometric methods and highlight the importance of function-based and context-aware frameworks.